Diversitas Vegetasi dan Kontribusi Ketahanan Pangan Agroforestri Homegarden Berbasis Gaharu (Gyrinops Versteegii) di Bantul, Yogyakarta - Rawana; Woesono, Hastanto Bowo; Falah, M. Darul (Jurnal Wana Tropika, 2025)
Agarwood agroforestry represents a land management system that combines agarwood-producing plants with food crops as a strategy for diversifying community food security sources. This study aimed to analyze the composition and species diversity of agarwood agroforestry components and evaluate their contribution to food security through food crop diversification. The research was conducted in Parangtritis Village, Kretek Sub-district, and Sawo Hamlet, Banguntapan Sub-district, Bantul Regency, Special Region of Yogyakarta, using systematic sampling method with 10 plots sized 20×20 m² (7 plots in Parangtritis, 3 plots in Sawo). Parameters measured included species composition, vegetation structure, and plant utilization for food security. Parameters measured in this study were: species, number, and plant benefits. Plant species identification used Steenis (1988) reference book. Species diversity index employed Shannon's index formula. The research findings revealed 24 tree species within 22 genera and 18 families with a total of 296 individuals. Of this number, 17 species (70.8%) contributed directly to food security, comprising: 15 fruit-producing species, 1 vegetable species, 1 oil-producing species, and 4 medicinal plant species. Shannon diversity indices in Parangtritis and Sawo were 1.46 and 1.87 respectively (moderate category), with evenness indices of 0.59 and 0.65 (moderate category). Species richness in Sawo (R=4.12) was higher compared to Parangtritis (R=2.02). The agarwood-based homegarden agroforestry system proved capable of providing sustainable food diversification with varied harvest seasons ensuring year-round food availability, thus having potential as a community-based food security model.